Space and communities in Byzantine Anatolia : papers from the fifth International Sevgi Gönül Byzantine Studies Symposium - Uluslararası Sevgi Gönül Bizans Araştırmaları Sempozyumu 2019 : Istanbul, Turkey); Kontogiannis, Nikos D. (Istanbul : Koç University Press, 2021)
"This volume collects twenty-six papers on Byzantine-period Anatolia that were presented at the Fifth International Sevgi Gönül Byzantine Studies Symposium held in June 2019. The sections of hte book focus on subjects including landscape dynamics, settlements and communication, regional networks, cityscapes, private and sacred space, and cultural interactions and identities. The essays cover a wide period, ranging from the third to the fifteenth centuries"--Back cover.
Landscape dynamics in Byzantine Anatolia. Remarks on history, environment, and climate in Byzantine Anatolia : comments on a complex landscape / John Haldon -- Rural settlements in Cilicia Secunda during the Late Antiquity and Early Byzantine periods : V-VI centuries / Mustafa Hamdi̇ Sayar -- Constantia and its hinterland : picturing the Syrian Orthodox community through material remains / Eli̇f Keser-Kayaalp. -- Settlements and communication in Byzantine Anatolia. Settlement pattern in the Meander Delta during the Byzantine Period / Jesko Fildhuth -- Behind the walls and in the countryside. Reconstructing Byzantine settlements and their environments in Anatolia : the case of the southern Troad / Beate Böhendorf-Arslan -- Harbor cities as interfaces of maritime and terrestrial communication systems in Late Antique and medieval western Anatolia / Andreas Külzer -- "I am going home by sea / for the first time in years" : urban-like coastal spaces across the early medieval Mediterranean / Luca Zavagno. Documenting regional networks in Byzantine Anatolia. Reshaping Byzantine Bithynia, or connecting archaeology and history online : a preliminary report on the Mapping Byzantine Bithyna Online (MBBO) project / Julie Curie, Olivier Delouis -- A selection of Byzantine lead aeals from the Adnan Aci Collection / Vera Bulgurlu -- Roman and Late Roman aettlement in the Demirci Valley, Sinop (Turkey) : a reconsideration / Owen Doonan, Anna Smokotina, Krzysztof Domzalski. Cityscapes in Byzantine Anatolia. Epigraphy of contested spaces : doctrinal identities, imperial and local agencies in an inscribed letter of Justinian (IEph 1353) / Arkadiy Avdokhin -- Amorium and the ever-changing urban space : from Early Byzantine provincial city to Middle Byzantine provincial capital / Nikos Tsivikis. Private and sacred Space in Byzantine Anatolia. Creating private space : living areas in the Late Antique cities of Asia Minor / Inge Uytterhoeven -- A Late Antique pilgrimage church at the harbor canal of Ephesus and its interaction with its religious center / Katinka Sewing -- Wreck the temple, taise the church? Christianization of the urban landscape / Burcu Ceylan, Eli̇f Karabacak -- The regional paradigm in early Christian art and architecture : the case of Anatolia / Philipp Niewöhner. Cultural interactions and identities in Byzantine Anatolia. Interactions between ceramic designs and millefiori glassmaking in Anatolia and its neighbors / Henry Maguire -- Belief, ritual, and social identity in Byzantine Anatolia : the testimony of mass- produced metalwork / Brigitte Pitarakis. Byzantine Anatolia through the lens of a central province : Cappadocia. Still a new land for art history? / Robert Ousterhout -- The imperial cult in Middle Byzantine art: Cappadocia and Constantinople / Lynn Jones -- The fortification wall at Selime and community identity in the Peristrema Valley, Cappadocia, (tenth-eleventh centuries) / Veronica Kalas -- Rescue excavations of the church of Sts. Constantine and Helena at Aktaş (Andaval, Andabalis), Niğde: 1996-2019 / Saci̇t Pekak. Liminal spaces: Byzantine Anatolia and beyond. Crossing the border : shifting identities in Byzantine Anatolia in the eleventh and twelfth centuries / Dimitri Korobeinikov -- Jews, Christians, and Jalal-al-Din Balkhi Rumi / Rustam Shukurov -- Muslim-Turkish politics of "spatial" control : the formation of settlement and public space in Manisa and Birgi (fourteenth century) / Alexander Beihammer -- Spatial control and the formation of public space in between Byzantium and the Turkish Beyliks : fourteenth century Manisa and Birgi (two case studies in archaeology of art) / Myrto Veikou.
Includes bibliographical references (pages 503-562) and indexes.
Keywords: Byzantine Empire -- Civilization -- Congresses; Byzantine Empire -- Court and courtiers -- History -- Congresses; Byzantine Empire -- History -- Congresses; Civilization, Medieval -- Congresses; Empire byzantin -- Civilisation -- Congrès.; Empire byzantin -- Histoire -- Congrès.; Civilisation médiévale -- Congrès.; Civilization; Civilization, Medieval; Courts and courtiers; Byzantine Empire; Conference papers and proceedings; History